The effects of age on the spontaneous low-frequency oscillations in cerebral and systemic cardiovascular dynamics. - Peng, T; Ainslie, P; Cotter, J; Murrell, C; Thomas, K; Williams, M; George, K; Shave, R; Rowley, AB; Payne, S (2008)
Although the effects of ageing on cardiovascular control and particularly the response to orthostatic stress have been the subject of many studies, the interaction between the cardiovascular and cerebral regulation mechanisms is still not fully understood. Wavelet cross-correlation is used here to assess the coupling and synchronization between low-frequency oscillations (LFOs) observed in cerebral hemodynamics, as measured using cerebral blood flow velocity (CBFV) and cerebral oxygenation (O2Hb), and systemic cardiovascular dynamics, as measured using heart rate (HR) and arterial blood pressure (ABP), in both old and young healthy subjects undergoing head-up tilt table testing. Statistically significant increases in correlation values are found in the interaction of cerebral and cardiovascular LFOs for young subjects (P<0.01 for HR-ABP, P<0.001 for HR-O2Hb and ABP-O2Hb), but not in old subjects under orthostatic stress. The coupling between the cerebrovascular and wider cardiovascular systems in response to orthostatic stress thus appears to be impaired with ageing.